HD DVD substrates for surface enhanced Raman spectroscopy analysis: fabrication, theoretical predictions and practical performance. Issue 50 (4th May 2016) - Radu, A. I.; Ussembayev, Ye. Ye.; Jahn, M.; Schubert, U. S.; Weber, K.; Cialla-May, D.; Hoeppener, S.; Heisterkamp, A.; Popp, J.
Abstract : Commercially available HD-DVD templates have been used to theoretically predict the occurrence of surface plasmons supermodes which improve the detection of surface enhanced Raman signals. Abstract : Commercial HD DVDs provide a characteristic structure of encoding pits which were utilized to fabricate cost efficiently large area SERS substrates for chemical analysis. The study targets the simulation of the plasmonic structure of the substrates and presents an easily accessible fabrication process to obtain highly sensitive SERS active substrates. The theoretical simulation predicted the formation of supermodes under optimized illumination conditions, which were verified experimentally. First tests of the developed SERS substrates demonstrated their excellent potential for detecting vitamin A and pro-vitamin A at low concentration levels.